2019
DOI: 10.1212/wnl.0000000000008627
|View full text |Cite
|
Sign up to set email alerts
|

Statins for neuroprotection in spontaneous intracerebral hemorrhage

Abstract: Statins, a common drug class for treatment of dyslipidemia, may be neuroprotective for spontaneous intracerebral hemorrhage (ICH) by targeting secondary brain injury pathways in the surrounding brain parenchyma. Statin-mediated neuroprotection may stem from downregulation of mevalonate and its derivatives, targeting key cell signaling pathways that control proliferation, adhesion, migration, cytokine production, and reactive oxygen species generation. Preclinical studies have consistently demonstrated the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
3
35
0
1
Order By: Relevance
“…Several studies in animal models of spontaneous intracerebral hemorrhage that have been treated with statins have improved neurological function, reduced cerebral edema effects, increasing angiogenesis, and neurogenesis, and have decreased the infiltration of inflammatory cells. This supports the possible neuroprotective effects of statins (55)(56)(57).…”
Section: Discussionsupporting
confidence: 80%
“…Several studies in animal models of spontaneous intracerebral hemorrhage that have been treated with statins have improved neurological function, reduced cerebral edema effects, increasing angiogenesis, and neurogenesis, and have decreased the infiltration of inflammatory cells. This supports the possible neuroprotective effects of statins (55)(56)(57).…”
Section: Discussionsupporting
confidence: 80%
“…First, our findings indicate that it is reasonable to manage the low-and intermediate-risk patients according to the current AHA/ASA guidelines and a nihilistic clinical response should never be taken, although ICH on top of allo-HSCT has traditionally been considered fatal 3 . Second, the dismal prognosis of high-risk patients shows that the treatments currently in use are not sufficient for them and novel treatments for ICH may be considered, which include minimal invasive surgery (MIS), novel hemostatic agents and neuroprotective agents 36,[58][59][60][61][62][63][64][65][66][67][68][69] (Supplemental Table 4). The DCA results also showed that it would be beneficial to use the LAWS score to aid clinicians in selecting patients at higher risk of early mortality and in more urgent need of novel ICH treatments other than the standard ones [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…In mice with embolic stroke, low atorvastatin doses are able to induce the expression of vascular endothelial growth factor (VEGF), thus promoting neovascularization, and improve neurological function by enhancing synaptogenesis and proliferation of neural progenitor cells ( 10 ). Neuroprotective effects of statins, including antioxidative, anti-inflammatory, angiogenic, neurogenic, and antiapoptotic properties, have also been demonstrated in animals with hemorrhagic stroke ( 37 ). All these findings led to hypothesized that statin administration may positively influence cerebral repair after injury acting on neurogenesis and angiogenesis ( 7 , 9 , 10 , 16 , 36 ).…”
Section: Discussionmentioning
confidence: 99%